Digital Security Awareness Level of Boarding School Based Islamic Junior High School Students in Central Lampung - Radinal Fadli; Dwi Wahyudi; Fivia Eliza (Juwara: Jurnal Wawasan dan Aksara, 2026)
The increasing use of the internet and information technology devices among students has made digital security awareness an important issue in educational environments. This study aims to analyze the level of digital security awareness among students of a boarding school–based Islamic junior high school in Central Lampung. A descriptive quantitative approach was employed, with the population consisting of all active students in grades VII–IX who had used the internet for at least one year. The study involved 40 students selected through purposive sampling. The research instrument was an objective multiple-choice test covering several aspects of digital security. The results show that students’ awareness is not evenly distributed across all aspects. Awareness of Viruses and Malware (75%) and Cyberbullying (70%) fell into the Sufficient category, indicating a basic understanding but still requiring reinforcement. In contrast, awareness of Artificial Intelligence (40%), Online Grooming (44%), and Phishing & Scams (47%) was categorized as Poor, highlighting the need for serious attention and targeted educational interventions. These findings emphasize the importance of implementing digital security literacy programs, particularly concerning contemporary digital threats, to better prepare boarding school students for the increasingly complex risks of cyberspace. Academically, this study contributes to the growing literature on digital security awareness within Islamic educational settings and highlights the need for integrating structured cybersecurity literacy into boarding school curricula. Furthermore, the findings may serve as a reference for future studies and educational policymakers in developing more contextual and sustainable digital security education programs.